Accuracy of MRCP in Comparison with ERCP for Diagnosing Hepato-Pancreatico-Biliary Pathologies. - Murtaza Gondal,Sumera Mushtaq Ch, Ishtiaq Ahmad, Tassawar Hussain, Shomaila Awan,Kiran Fatima, Murtaza Gondal,Sumera Mushtaq Ch, Ishtiaq Ahmad, Tassawar Hussain, Shomaila Awan,Kiran Fatima (Journal of Rawalpindi Medical College, 2018)
Background: To determine the accuracy of magnetic-resonance-cholangiopancreatography (MRCP) in comparison with the endoscopic-retrograde-cholangiopancreatography (ERCP) in the diagnosis of bile duct pathologies. Methods: Patients with suspected pancreaticobiliary pathologies having a clear indication for ERCP were included in this prospective study. MRCP was performed, using a torso phased-array coil.ERCP was performed by duodeno-videoscope and general electric fluoroscopy. MRCP was reviewed by the radiologist who was blinded to the ERCP results.The ERCP was interpreted by an experienced consultant gastroenterologist also blinded to the MRCP results. Results of hepato-pancreatico biliary system from both techniques were compared, according to the pathology found, e.g. choledocholithiasis, pancreatico-biliary strictures, and dilatation. The sensitivity, specificity, and positive and negative predictive values were calculated. Statistical significance was set at p<0.05, with 95% confidence intervals. Results. MRCP had sensitivity, specificity, positive and negative predictive values of 87%, 80%, 83.3% and 84.2% respectively for choledocholithiasis, which correlates well with results obtained in other parts of the world. Conclusion. MRCP has high diagnostic accuracy for bile duct calculi and is a useful non-invasive technique to diagnose biliary pathologies and avoids unnecessary ERCPs and its complications.